2010
DOI: 10.1080/13504850903425108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of determinants of airline choice: profiling the LCC passenger

Abstract: This article analyses the socioeconomic characteristics and trip attributes that influence or correlate with airline choice using a database of 20 000 passengers. One of the conclusions that should be highlighted is the lack of significance of socioeconomic variables except when the passenger is non-Spanish and the frequency with which one travels. And yet there are many trip attributes that condition the choice. Of these the following can be highlighted: the destination, the purpose, the need to transfer to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…This finding is even more important when we take into account that LCCs do not usually offer generous compensation packages in the form of accommodation, meals or alternative transport for passengers who endure long delays (eventualities that, according to Castillo-Manzano and Marchena-Gómez (2010), are better catered for by network carriers). This finding is therefore a clear incentive for passengers to take out ample travel insurance which would provide them with compensation, given the greater likelihood of being subject to a long delay, either the policies sold by the LCCs themselves with their tickets, or those linked to premium credit cards (gold, platinum or similar).…”
Section: Discussionmentioning
confidence: 79%
“…This finding is even more important when we take into account that LCCs do not usually offer generous compensation packages in the form of accommodation, meals or alternative transport for passengers who endure long delays (eventualities that, according to Castillo-Manzano and Marchena-Gómez (2010), are better catered for by network carriers). This finding is therefore a clear incentive for passengers to take out ample travel insurance which would provide them with compensation, given the greater likelihood of being subject to a long delay, either the policies sold by the LCCs themselves with their tickets, or those linked to premium credit cards (gold, platinum or similar).…”
Section: Discussionmentioning
confidence: 79%
“…A priori, both simple data observation (see Appendix A) and earlier studies (see Castillo-Manzano & López-Valpuesta, 2010) identify LCCs as great drivers of strategies that prevent the intermediation of travel agencies, meaning that travel agencies might be expected to present negative correlations. That is, it could be anticipated that travel company managers will give lower scores than other managers, especially regarding the contribution made by LCCs to conference tourism, as it is not unheard of for travel agency representatives to openly defend the greater suitability of network carriers for conference tourism in the media.…”
Section: Methodsmentioning
confidence: 98%
“…This is a tendency that will, foreseeably, increase in the future as the degree of autonomy in Spanish airport decentralization continues to grow in a process similar to that already seen in the Spanish ports and harbor system (see Castillo-Manzano, López-Valpuesta, & Gonzalez Laxe, 2010, regarding the Spanish Ports and Harbor System port devolution process).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…While passenger choice of LCC or FSC has been examined in European shorthaul markets (Castillo-Manzano & Marchena-Gómez, 2011;Forgas et al, 2010;Kuljanin & Kalić, 2015;Kurtulmuşoğlu, Can, & Tolon, 2016;Mason, 2001;Mikulić & Prebežac, 2011;O'Connell & Williams, 2005), recent passenger choice studies comparing LCC or FSC have not been found in the U.S. Additionally, the findings of existing scholarly research on passenger choice of LCC or FSC in short-haul markets may not be generalizable to long-haul markets, and existing research has not been found for LCLH versus FSC in any air market.…”
Section: Existing Passenger Survey Researchmentioning
confidence: 99%